The Social Mortality Gradient and Social Mobility: New Insights from Early Scottish Chartered Accountants - Merkoulova, Yulia; Paisey, Catriona (The Accounting Review, 2024)
ABSTRACT This paper examines the prevalence and benefits of upward social mobility in the early accountancy profession by analyzing the lifespan of chartered accountants admitted to membership in Scotland between 1853 and 1940. We find that 76 percent of the chartered accountants in our sample experienced upward social mobility, a greater percentage than found in previous studies. The chartered accountants in our sample experienced an average life expectancy premium of approximately three years over the general population, irrespective of social origins, and were less likely to die from most preventable causes than the general population. Upwardly mobile chartered accountants achieved lifespans consistent with their achieved professional status rather than their previous social class. While the findings confirm the existence of a social mortality gradient, the increase in longevity is likely attributable to the superior resources of higher social class and other factors affecting self-selection into the accountancy profession. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: I1; I3; M4; N3.